The independent and combined effects of single-child status and ideal lifestyle on clustered cardio-metabolic risk factors among Chinese children and adolescents - Dang, Jiajia; Ma, Ning; Liu, Yunfei; Zhong, Panliang; Shi, Di; Cai, Shan; Dong, Yanhui; Zou, Zhiyong; Ma, Yinghua; Song, Yi; Ma, Jun (Frontiers in Nutrition, 2022)
Background: Cardio-metabolic risk factors (CMRFs) represent the accumulation of metabolic abnormalities, significantly increasing the likelihood of cardiovascular diseases. Although studies assessed the independent association of single-child status and lifestyle risk factors with components of CMRFs or clustered CMRFs, little has been known about the combined effect of single-child status and lifestyle on clustered CMRFs as well as sex differences. Methods: Data was collected from a cross-sectional survey conducted in September 2013 in China. A total of 13,859 children and adolescents aged 7–18 years with blood samples were included. Anthropometric measurements and serum biochemical indexes were collected to assess clustered CMRFs, while questionnaires were used to obtain single-child status, lifestyle information, and characteristics of children and their parents. Mixed effect logistic regression was applied to analyze the independent and the combined effects of single-child status and ideal lifestyle category on clustered CMRFs. Results: The prevalence of clustered CMRFs was 3.4%, with a higher prevalence in boys (4.0%) than girls (2.7%). Children and adolescents with clustered CMRFs had a higher proportion of single children (76.6% vs. 69.7%) and unfavorable lifestyles (62.1% vs. 29.2%) compared with their peers with non-clustered CMRFs. Both single children (OR=1.67, 95% CI: 1.32–2.11) and unfavorable lifestyles (OR=9.03, 95% CI: 6.26–13.02) were associated with an increased risk of clustered CMRFs. The risk of clustered CMRFs increased significantly (OR=12.79, 95% CI: 6.67–24.52) when single children and an unfavorable lifestyle were combined, which was almost neutralized (OR=1.33, 95% CI: 0.63–2.82) when single children adhered to a favorable lifestyle. However, no sex differences were observed in this study. Conclusions: Single children with unfavorable lifestyles were associated with an obvious risk of clustered CMRFs, which might be partially offset by expanding family size (the number of siblings) or establishing a favorable lifestyle. A birth-friendly social environment as well as a family environment with a favorable lifestyle are encouraged in China.